Effect of Self-Efficacy Integration With Family Support Program on Behaviors to Prevent Heart Attack Recurrence in Patients With Acute Myocardial Infarction After Revascularization - Potjamanpong, Pattarasiri; Kritpracha, Charuwan; Chinnawong, Tippamas (Journal of Research in Nursing-Midwifery and Health Sciences, 2015)
This quasi-experimental research aimed to examine the effect of self-efficacy integration with family support program on behaviors to prevent heart attack recurrence in patients with acute myocardial infarction after revascularization at a tertiary hospital in Southern Thailand. Fifty - two subjects were purposively selected and randomized into two groups; control and experimental. Patients in the control group received standard treatment and nursing care. It is coordinated Bandura’s self-efficacy model and family support were used to guide intervention of this study with a pretest-posttest quasi experimental design. Patients in the experimental group received the program given by the researcher comprising 1) knowledge providing, counseling, and facilitating family to support patient’s behaviors to prevent heart attack recurrence; 2) goals setting for modification of behaviors; 3) watching video of a patient who was successful in preventing recurrence of the disease; and 4) Used making word persuasion and follow the phone result as the second, third and fourth week.The research instruments were 1) demographic questionnaires 2) illness questionnaires, and 3) behaviors to prevent heart attack recurrence questionnaires. The scale-level content validity index of the preventing heart attack recurrence questionnaires validated by three experts was .94. Reliability was tested and yielded Cronbach’s alpha coefficient of .73. The data were analyzed using descriptive statistics and chi-square. Repeated measures ANOVA and independent t-test were used to analyze differences in mean score of behaviors to prevent heart attack recurrence. The results revealed that: The mean score of behaviors to prevent heart attack recurrence in the experimental group after receiving self-efficacy integration with family support program was statistically significantly higher than the control group ( t = -2.51, p < .05) The mean score of behaviors to prevent heart attack recurrence in the experimental group after receiving self-efficacy integration with family support program was statistically significantly higher than before receiving the information ( F = 64.54, p < .001) The results of this study indicate nurses should implement this self-efficacy integration with family support program in their practice in order to prevent heart attack recurrence in patients with acute myocardial infarction after revascularization.